Evaluasi Kinerja Saham Tercatat di Bursa Efek Indonesia Menggunakan Model Sharpe dan Model M² dalam Periode 2003–2007 - Mohamad Samsul (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research is intended to find out the performance of stock listed in Indonesia Stock Exchange during period of 2003 to 2007 by using M²’s model and Sharpe’s model. The other objective of this research is to find empirical evidence for the different performance of stock between M²’s model and Sharpe’s model.. This research used a number sample of 301 kind of stocks which already listed since before end of the year of 2002 up to end of 2007. This research used monthly data of : stock index prices, market index LQ45, and risk free rate of Indonesia Bank Certificate. Four hypothesis are in this research: (1) the monthly excess return of stock due to M²’s model and Sharpe’s model is different; (2) the risk of stock due to M²’s model and Sharpe’s model is different; (3) the reward to variability ratio due to M²’s model and Sharpe’s model is different; (4) the M² value due to M²’s model and Sharpe’s model is different. The finding of this research show that the number of undervalued stock is 5 stocks and 252 stock according to rank of M²’s model and Sharpe’s model respectively.which the details result as below: The monthly excess return of stock is 0,074 and 0,038 due to M²’s model and Sharpe’s model respectively. The difference is statistically not significant. The risk of stock of 0,155 and 0,237 due to M²’s model and Sharpe’s model respectively. The difference is statistically significant. The reward to variability ratio is 0,478 and 0,166 due to M²’s model and Sharpe’s model respectively. The difference is statistically significant. The M² value is 0,0036 and (0,0157) due to M²’s model and Sharpe’s model respectively. The difference is statistically significant.Keywords: Sharpe’s model, M²’s model, reward to variability ratio, M² value.